Omnidirectional antenna for WLAN application - Phoon, Clarence Jian Zhong. (2012)
The design, simulation, fabrication and measurement of a 5GHz horizontally polarized omnidirectional antenna for WLAN application are presented. The antenna adopts the structure of a slot antenna with 2 side grounds. CST Microwave Studio Suite was used for simulation purposes. The finalized designed antenna is fabricated on a Taconic TL-6 substrate. This paper examines how changes in various parameters affect the S-Parameter curve and radiation pattern of the antenna. The E field of the antenna was slightly less omnidirectional than expected at the azimuth angle of plus minus 60 degrees. However, the gain of the antenna was better than expected at 5.0-5.2GHz.